Childhood acute erythroleukemia diagnosis by flow cytometry - Anjali Sharma; Gurdeep Buxi; Ritika Walia; Raj Bala Yadav; Sunita Sharma (Wolters Kluwer Medknow Publications, 2011)
Acute erythroid leukemia in children is very rare. Here is a case of erythroleukemia in a child of age 1.5 years, which was diagnosed on peripheral smear, bone marrow examination, cytochemistry but was confirmed on immunophenotyping. CD45 versus side scatter demonstrated blast population (29%) expressing CD45 of variable intensity (dim to negative). The myeloid nature of blast population showed bright expression of cytoplasmic myeloperoxidase (MPO), heterogenous positivity of CD117 and dim expression of CD13, CD33. These blasts also showed bright positivity for CD71 which showed erythroid nature of blasts. Flow cytometry can be comprehensive enough to completely subtype cases of leukemias/myelodysplastic syndromes, polycythemia rubra vera, non-neoplastic conditions like reactive erythroid hyperplasia following immunosuppressive therapy or viral infections or nutritional deficiencies, unlyzed RBCs or thrombocytosis which may mimic acute erythroid leukemia on flow cytometry.